DEVELOPMENT OF TEACHING MATERIALS BASED ON CASE-BASED LEARNING ON STATISTICS - Dewi Nur Fauzia; Dindin Sobiruddin; Khairunnisa Khairunnisa (ALGORITMA: Journal of Mathematics Education, 2021)
This research is motivated by the limited use of mathematics teaching materials in schools. This research aims to develop teaching materials based on Case-Based Learning on Junior High School statistics in Grade VIII. This teaching material has systematically arranged using Case-Based Learning steps. The Teaching Materials were developed to consist of 3 learning activities: 1)  Data Analysis, 2) Mean, Median, Mode, and 3) Range and Quartile. The research method used is the research and development method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Teaching materials go through the validation and limited trial stage on five aspects: content feasibility, language, presentation, graphics, and Case-Based Learning. The results showed that the teaching materials developed have Very Valid criteria based on the Validator's assessment. It is getting a V Aiken coefficient of 0.8890, while the students' responses resulted in 82.33% on very feasible criteria. So we can conclude that the Case-Based Learning teaching materials on Statistics material are suitable to be used as a support for learning mathematics in schools.